(untitled) (Research, Society and Development, 2021)
It is the State’s duty to promote the common good without any form of discrimination, so that the social function of the city is efficiently fulfilled, considering that such function is constituted by the security that everyone enjoys housing, leisure, public services and traffic on the roads. However, the presence of barriers imposed by mistaken architectural projects is still quite common in the country’s buildings. Thus, ensuring the citizenship and dignity of all Brazilians results in seeing buildings in the architectural project as instruments that guarantee the right to come and go. From this perspective, this research aimed to discuss accessibility as a tool for social inclusion in the built environment, in order to highlight the usefulness of considering universal accessibility as a fundamental right. The research methodology adopted was the qualitative bibliographic research model. Thus, it was possible to conclude that the guarantee of an accessible environment is of great importance for the social life of people with special needs or with reduced mobility, as it promotes quality of life and guarantees the full exercise of their citizenship.